2009
DOI: 10.1021/ja902534b
|View full text |Cite
|
Sign up to set email alerts
|

Motion of the Zinc Ions in Catalysis by a Dizinc Metallo-β-Lactamase

Abstract: We report rapid-freeze-quench X-ray absorption spectroscopy of a di-zinc metallo-β-lactamase (MβL) reaction intermediate. The Zn(II) ions in the dinuclear active site of the S. maltophilia Class B3 MβL move away from each other, by ~ 0.3 Å after 10 ms of reaction with nitrocefin, from 3.4 to 3.7 Å. Together with our previous characterization of the resting enzyme and its nitrocefin product complex, where the Zn(II) ion separation relaxes to 3.6 Å, these data indicate a scissoring motion of the active site that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
31
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 15 publications
8
31
0
1
Order By: Relevance
“…Inclusion of a metal-metal interaction at 3.81 Å to the model improved the fit residual by 34% (Figure S4 and Table S4). A similar increased metal-metal distance was previously observed in the ZnZn-L1/nitrocefin sample quenched at 10 ms. 18 Our stopped-flow kinetic studies suggest that the sample quenched at 10 ms contains predominantly enzyme-intermediate complex (Figure 2). These data strongly suggest that there was no change in the coordination number of either metal ion in the sample quenched at 10 ms.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Inclusion of a metal-metal interaction at 3.81 Å to the model improved the fit residual by 34% (Figure S4 and Table S4). A similar increased metal-metal distance was previously observed in the ZnZn-L1/nitrocefin sample quenched at 10 ms. 18 Our stopped-flow kinetic studies suggest that the sample quenched at 10 ms contains predominantly enzyme-intermediate complex (Figure 2). These data strongly suggest that there was no change in the coordination number of either metal ion in the sample quenched at 10 ms.…”
Section: Resultsmentioning
confidence: 76%
“…20 In contrast, RFQ-EXAFS studies on ZnZn-L1 indicated an increase in the average coordination number of Zn(II) in the sample freeze quenched at 10 ms and in the product complex, as compared to the resting enzyme. 18 The EXAFS studies indicated an increase in the metal-metal distance in L1 after 10 ms of reaction with nitrocefin. The EXAFS studies indicated formation of a Zn-S interaction in the product complex, 18, 23 afforded by rotation around the C6-C7 bond after hydrolysis.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…50 This plasticity can be required for the different steps of the full catalytic cycle or it can also promote catalytic promiscuity. In particular, the mechanistic implication of the motion of the zinc ions dizinc metallo-beta-lactamases was already observed by Breece et al 51 Thus, keeping in mind that the structural experimental evidences are based on the apo enzyme or on a complex not corresponding to the reactants or intermediate, none of the obtained structures could be, a priori, discarded. Hamiltonian, was found that movement of Zn ions is dramatic from R to TS.…”
Section: Discussionmentioning
confidence: 99%
“…[101] It was shown that loop movements occur during catalysis, and it has previously been shown that there are metal-metal distance changes between resting, intermediate-bound, and product-bound states; it seems possible that these two factors are linked. [102][103][104] It is thought that the flexibility in coordination states observed in MbL enables hydrolysis with different compounds, but at the cost of efficient hydrolysis. [100] The promiscuous reactions that different MbLs catalyse generally have lower k cat , where it is hypothesised that promiscuous substrates may not be well positioned relative to the nucleophilic hydroxide for catalysis.…”
Section: Active Site Changes and Activity Divergencementioning
confidence: 99%